2009
DOI: 10.1007/s12149-009-0310-0
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal transit scintigraphy and structured questionnaire in patients with systemic sclerosis with endoscopically proven reflux esophagitis

Abstract: Objectives: Esophageal complication is common in patients with systemic sclerosis (SSc). The relationship between gastroesophageal reflux (GER) symptoms and dysmotility was examined in endoscopically confirmed patients with suspected of having reflux esophagitis. Methods: A total of 32 patients with limited and diffuse type SSc (lSSc, dSSc) were examined based on a structured questionnaire score (QS) of GER symptoms, retention fraction of esophageal scintigraphy at 90 seconds (R90) and gastric emptying time. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In this study about half of the patients with definite SSc showed abnormal transit, which was less than that of the histological examination. Although GERD symptoms are considered to be common complications in SSc patients, we have found that some patients showed dysmotilitydominant symptoms rather than GERD symptoms using a questionnaire method [19]. It is conceivable that slight histological abnormality did not directly appear as a transit abnormality, and the dysmotility would become evident after certain stages.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In this study about half of the patients with definite SSc showed abnormal transit, which was less than that of the histological examination. Although GERD symptoms are considered to be common complications in SSc patients, we have found that some patients showed dysmotilitydominant symptoms rather than GERD symptoms using a questionnaire method [19]. It is conceivable that slight histological abnormality did not directly appear as a transit abnormality, and the dysmotility would become evident after certain stages.…”
Section: Discussionmentioning
confidence: 77%
“…An esophageal transit study was performed as described [11,19]. The study was performed under fasting condition for at least 6 hours, and current medications that may alter esophageal transit were documented.…”
Section: Esophageal Transit Studymentioning
confidence: 99%
See 1 more Smart Citation
“…OPES has been used since 1970 for the study of the swallowing function in patients with head and neck disease including patients with neuromuscular disorders. Several studies have suggested a higher sensibility of OPES compared to esophageal manometry and to barium swallow X‐ray …”
Section: Discussionmentioning
confidence: 99%
“…Such high prevalence is probably due to abnormal motility characterized by the loss of peristalsis in distal esophagus and lower esophageal sphincter pressure [10,11]. On the other hand, it was reported that neither disease duration nor the type of SSc shows meaningful association with the presence of RE [12,13]. Despite these several previous reports, evidence showing an association between RE and background factors of SSc patients is still inadequate.…”
Section: Introductionmentioning
confidence: 99%